CpG hypomethylation at proximal promoter and 5’UTR along with IL6 signaling loop associates with MYD88 upregulation in epithelial ovarian cancer - Junyang Li; Bingjie Mei; Yi Zhu; Jianmei Huang; Meiying Li; Dengfeng Wang; Jianming Huang; Guonan Zhang (Scientific Reports)
Abstract MYD88 is an IL-6 primary response gene and, its upregulation of expression has been shown to be a poor prognostic factor in epithelial ovarian cancer (EOC). We investigated the effects of CpG methylation at the proximal promoter/5’UTR and IL-6/SP1/IRF1 signaling on upregulation of MYD88 and prognosis in EOC. We assessed CpG methylation at the proximal promoter/5’UTR of MYD88 using bisulfite sequencing/PCR in 103 EOC patients, 28 normal ovarian tissues and two EOC cell lines with differential expression of MYD88 and identified the impact of the level of CpG methylation on MYD88 upregulation by SP1/IRF1 with knockdown or blockade of IL-6. The proximal promoter/5’UTR of MYD88 was significantly hypomethylated in 75 EOC tissues compared to 28 normal ovarian tissues (P < 0.001). CpG hypomethylation was relevant to MYD88 upregulation in 75 EOC cases (R2 = 0.4376; P < 0.001). Of them, 38 cases with m5CpGlow/MYD88high/IL-6high were associated with reduced progression-free/overall survival compared to 37 cases with m5CpGhigh/MYD88low/IL-6low (P < 0.01). Knockdown of IL-6 or blockade with IL-6 receptor McAb attenuated MYD88 upregulation by SP1/IRF1 signaling in EOC cells with MYD88high (P < 0.001). In conclusion, CpG hypomethylation at the proximal promoter/5’UTR contributes to MYD88 upregulation in EOC via IL-6/SP1/IRF1 pathway.